DEVELOPMENT OF TEACHING MATERIALS WITH PYROLYSIS TOOLS TO OVERCOME STUDENT'S UNCEPTIONAL MISCEPTIONS IN THE PHYSICS STUDY IN SMA LUBUKLINGGAU CITY - Endang Lovisia; Wahyu Arini (Universitas Negeri Medan, 2020)
This research purposed to develop teaching materials with pyrolysis tools at temperature and heat materials thatare valid, practical and effective. This type of research is R & D with the ADDIE model, the research subjects are 3 schools in SMA Kota Lubuklinggau in the high, medium and low categories. The research sampling technique used purposive sampling technique. From the three schools, a sample of 30 students was obtained, for each school there were 10 students as the sample. The 30 students have high, medium and low abilities. The validation obtained from the three material, language and media expert validators is that 80.49% of the teaching materials are in the very good category. Student response to teaching materials was 82.36% in the category of strongly agree. Student learning outcomes increased after being given a test of 5 questions, seen from tcount = 36.20 and ttable = 2.04 because tcount ≥ t table so it can be said that Ha is accepted and Ho is rejected. Therefore, the average value of the cognitive learning outcomes of students can be said to increase. And also get an n-gain score of 0.76 with high criteria. So that physics teaching materials using pyrolysis tools can be said to be valid, practical and effective.